Solution (1) :
Solution (a) :
step 1. Multiply the variable x with 13 .
step 2. Add 2 to it .
Solution (b) :
Step 1 : Subtract 2 from both sides : 13x + 2 - 2 = 41 - 2 = 39
Step 2 : Divide both the sides by 13 : 13x ÷ 13 = 39 ÷ 13 = 3
x = 3
Solution (2) :
Solution (a) :
Step 1. Subtract 3 from the variable .
Step 2. Divide the result by 5 .
Solution (b) :
![Step \: 1. \: add\: 3 \: to \: both \: the \: sides : (x - 3)/(5) + 3 = - 1 + 3</p><p>](https://img.qammunity.org/2021/formulas/mathematics/college/rwyo9ei28jtfpr49sha5wh6z4lcrloppnf.png)
Step 2 : Multiply both the sides by 5 : 5 × 1/5x = 5 × -2/5
x = -2